A 9‐year audit of fetal chest masses in an Australian maternal—fetal medicine cohort. Issue 3 (27th June 2019) - Gopikrishna, Saranya; Henry, Amanda; Kaur, Simren; Shand, Antonia W.; Jiwane, Ashish; Dyer, Kate; Welsh, Alec W.
Abstract: Introduction: To assess fetal vs. neonatal diagnoses, pregnancy outcomes and need for surgery in babies prenatally diagnosed with congenital pulmonary airway malformation (CPAM) or bronchopulmonary sequestration (BPS). Methods: Retrospective single‐centre cohort study of fetuses with a prenatal diagnosis of CPAM or BPS between 2006 and 2014. Data collected included serial antenatal ultrasound information and neonatal/infant diagnoses and outcomes. Results: Initial ultrasound diagnosis (n = 63) was CPAM in 51 and BPS in 12: nineteen (30%) fetuses had mediastinal shift and 2 (3%) had hydrops. All neonates with known birth outcome (n = 56) were liveborn. Final diagnosis in 52 infants (83%) with neonatal imaging and/or histopathology confirmed CPAM in 17/44 (39%) and BPS in 6/9 (67%). Of 34 prenatally suspected but unconfirmed CPAM lesions: 10 had no lesion on neonatal imaging, one no neonatal imaging performed, five confirmed BPS, 11 other lung/thoracic lesions, seven were lost to follow‐up. There was one infant death. 27/63 infants (43%) had post‐natal surgery. More neonates requiring neonatal respiratory support/resuscitation had surgery compared to those who did not (67% vs. 29%, P = 0.008). Patients with suspected CPAM or BPS on both initial and final ultrasound were more likely to have post‐natal surgical management than when a lesion was no longer visible on final antenatal ultrasound (68% vs. 23%, P = 0.001). Conclusions: Over 50% of antenatally suspected CPAM/BPS either regressed or had an alternate post‐natal diagnosis. Perinatal outcome was good, with the majority of neonates/infants conservatively managed. Persistently visible antenatal lesion and need for neonatal respiratory support predicted ultimate surgical management.